The Corsican shadow [compact disc, unabridged] - Cussler, Dirk (Cussler, Clive. Dirk Pitt adventure., 2023)
National Underwater and Marine Agency Director Dirk Pitt is on a diving expedition in the English Channel when he discovers a cache of uncut diamonds on a shipwreck. When the diamonds are stolen, Pitt and the NUMA agency find themselves up against a murderous cabal that soon reveals far more destructive plans than mere theft. Vital water treatment facilities around the globe are being targeted, placing the world's population in grave peril.